2021
DOI: 10.3390/ma14030517
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Epoxy Latexes on the Mechanical Behavior and Porosity Property of Cement Mortar with Different Degrees of Hydration and Polymerization

Abstract: In this study, an analysis of the influence of polymer modification on the mechanical behavior, porosity, and microstructure of mortar is carried out. Epoxy latexes contents of 5%, 10%, 15%, and 20% of cement were employed in the preparation of cement mortars based on the same workability. The specimens were subjected to dry, wet, and wet–dry curing regimes. Compressive strength, flexural strength, Mercury intrusion porosimetry (MIP), and scanning electronic microscope (SEM) tests were conducted to analyze the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 54 publications
(70 reference statements)
1
16
0
Order By: Relevance
“…Additionally, the lower activity index of mineral additives (compared to Cement AI) used further reduced the compressive strength of tested components. This is in agreement with reported research which concluded that the reduction in compressive strength could be due to both the decelerating effect of polymer modifiers on cement hydration and the volume change of the mortar [ 51 ].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Additionally, the lower activity index of mineral additives (compared to Cement AI) used further reduced the compressive strength of tested components. This is in agreement with reported research which concluded that the reduction in compressive strength could be due to both the decelerating effect of polymer modifiers on cement hydration and the volume change of the mortar [ 51 ].…”
Section: Resultssupporting
confidence: 93%
“…and M0) resulted in improved flexural strength. The increase in flexural strength may be due to the formation of a polymer film, which increases the strength of the binder interface between the cement hydration products and the aggregate [ 51 ]. However, by introducing mineral additives, this interface may be impaired due to either weakening of the formed polymer film or lower content of active silica in mineral additives [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nie and An [12] visualized the threshold theory by the selfcompacting paste (SCP) zone, which is the set of all points satisfying the theory. Higher costs, higher hydration heat, and greater shrinkage during drying may occur as a result of SCC with a large amount of cement [13][14][15]. erefore, mineral admixtures such as FA and LP are usually used to replace partial cement [16][17][18][19][20][21][22], which may reduce hydration heat, optimize the particle packing, and maintain the SCC workability [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%